DIFFERENTIATION IN MORPHOLOGICAL CHARACTERISTICS AND MOTOR SKILLS OF YOUNGER SCHOOL-AGE STUDENTS - Dževad Džibrić,; Alen Kapidžić,; Melika Muratović,; Jasmin Bilalić,; Tarik Ljubovic,; Sanjin Hodzic, (Sport Scientific And Practical Aspects, 2025)
Growth and development are indicators of good health, as well as a mirror of quality nutrition and quality of life. By monitoring growth and development, the relationship between motor abilities and morphological characteristics is recognized. The period of younger school age is characterized by strong growth and development of all anthropological dimensions, especially morphological and motor ones, which differ significantly in children, concerning adults. This transversal research aimed to determine the differences in morphological characteristics and motor abilities betweelower primary school students. The research was conducted on a sample of 1233 girls, I - IV grades of primary schools from the area of the City of Tuzla. The sample of variables consisted of a set of 10 tests to assess certain anthropological dimensions (5 morphological and 5 motors), appropriate to the age of the study population. Univariate analysis of variance with multiple comparisons was used to determine the differences in the studied spaces between students of different grades, with the applied post hock Bonferroni test. The obtained results showed that there are statistically significant differences in all applied variables (morphological and motor). between treated groups at the level of significance (p≤0.05). The results of the research draw attention to the importance of early stimulation of morphological-motor development and a healthy lifestyle in female students, which are characterized by regular physical activity and a healthy diet. Optimal levels of motor skills, well-developed fundamental motor skills and a healthy body structure are of great importance for health, quality of life-related to health and overall well-being of younger school-age students.